Effective surface passivation of Si surfaces by chemical deposition of (Al2O3)x(B2O3)1 − x thin layers. Issue 4 (20th December 2012) - Vitanov, Petko; Harizanova, Antoaneta; Ivanova, Tatyana; Perego, Michele; Stokkan, Gaute; Ulyashin, Alexander
Abstract In this work chemical liquid deposition from sol–gel solutions has been used to obtain thin (Al2O3)x(B2O3)1 − x dielectric films. Passivation of Si surfaces using these films has been studied. Morphological properties of thin films deposited on polished Si surfaces have been investigated by scanning electron microscopy (SEM) and atomic force microscopy (AFM) technique. Their chemical composition, structural and optical features have been analysed by X‐ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and ultraviolet‐visible (UV–VIS) spectroscopy. Results, obtained in this work, show that silicon surfaces can be effectively passivated by thin dielectric layers deposited from chemical solutions. The thin dielectric layers developed in his work, can be recommended as back side passivation coating for Si‐based solar cells.